Simulation of Second Harmonic Generation from Photonic Nanostructures Using the Discontinuous Galerkin Time Domain Method - Grynko, Yevgen; Förstner, Jens (Recent Trends in Computational Photonics)
We apply the Discontinuous Galerkin Time Domain (DGTD) method for numerical simulations of the second harmonic generation from various metallic nanostructures. A Maxwell–Vlasov hydrodynamic model is used to describe the nonlinear effects in the motion of the excited free electrons in a metal. The results are compared with the corresponding experimental measurements for split-ring resonators and plasmonic gap antennas.
Keywords: tet_topic_numerics; tet_topic_shg; tet_topic_meta